Dinamika Keberadaan Wisata Pintu Langit Desa Bengkaung Di Massa Covid 19 - Ida Ayu Vista Dewi (Widya Sandhi: Jurnal Kajian Agama, Sosial dan Budaya, 2020)
This research is intended to study the existence of tourism destination of the sky Gate in the phenomenon of COVID 19 in the village of Bengkaung Batulayar District, West Lombok Regency. The study was designed in a qualitative descriptive method. The results of the study gained that the development of tourism in the village can support the image and economy of the village so that it will create the developed villages in Indonesia. An economic base applied by tourism-oriented in the Sky Tourism tour can compete with villages in Indonesia. Also, community involvement that synergizes for the development of a sustainable tourism sector and the role of government that can provide adequate facilities for prospective tourists such as adequate roads, safety, and comfort of tourists, is the most effective way for Bengkaung village to be one of the developed villages and not left in Indonesia in the future.